2020
DOI: 10.1111/pedi.12973
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical profile of youth onset diabetes patients in India—Results from the baseline data of a clinic based registry of people with diabetes in India with young age at onset—[YDR‐02]

Abstract: Background We here report the demographic and clinical profile of the patients enrolled in the Indian Council of Medical Research funded Registry of people with diabetes in India with young age at onset (YDR) from 1 January 2000 to 31 July 2011. Methods The YDR registry recruits all diabetes cases (newly diagnosed or treated) reporting on or after 1 January 2000 with age of diagnosis ≤25 years, and residing within the assigned geographical area of the reporting centres. A baseline proforma was used to obtain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
3
15
1
Order By: Relevance
“…23 Although no data from India are available to compare the glycaemic control in children and adolescents with T1D on basis of their age, it is suggested that the incidence of T1D usually peaks between 10-14 years age, referred to as pubertal peaking in the Asian Indian population. 24 Moreover, the SEARCH study noted that amongst youth with T1D, mean HbA1c was 8.6% in the period 2002-2007, and statistically significantly higher in 2014-2019, at 8.7%, after adjustment for study site, age, sex, race/ethnicity, health insurance status, and disease duration. It was also found that mean HbA1c concentrations in T1D participants in the 10-14 years, 15-19 years, and 20-24 years age brackets were significantly higher in the current (2014-2019) cohort than the earlier (2002-2007) cohort.…”
mentioning
confidence: 99%
“…23 Although no data from India are available to compare the glycaemic control in children and adolescents with T1D on basis of their age, it is suggested that the incidence of T1D usually peaks between 10-14 years age, referred to as pubertal peaking in the Asian Indian population. 24 Moreover, the SEARCH study noted that amongst youth with T1D, mean HbA1c was 8.6% in the period 2002-2007, and statistically significantly higher in 2014-2019, at 8.7%, after adjustment for study site, age, sex, race/ethnicity, health insurance status, and disease duration. It was also found that mean HbA1c concentrations in T1D participants in the 10-14 years, 15-19 years, and 20-24 years age brackets were significantly higher in the current (2014-2019) cohort than the earlier (2002-2007) cohort.…”
mentioning
confidence: 99%
“…The proportion of T2DM among 603 patients with onset of diabetes <20 years of age was recorded in a 2008 multicenter publication as only 6% (with 89% T1DM and 3% FCPD) 19 . In contrast, in another multicenter study of 5546 patients with age of onset <25 years, Praveen et al 20 reported T2DM in 25% patients, with great regional disparity in this representation, ranging from 0% to 8.1% to as high as 39% and 43% in different participating centers. Childhood obesity is rising globally, as well as in India, and with this, it is inevitable that T2DM will increase in this age group 2,21 .…”
mentioning
confidence: 94%
“…[ 1 ] Youth-onset diabetes may not always be due to type 1 diabetes especially with the rising prevalence of early-onset type 2 diabetes mellitus (T2 DM), which was earlier considered as a disorder occurring only in the middle-aged or elderly. [ 2 3 ] In India, these data are collected by the Youth Diabetes Registry (YDR). The YDR collates data of people diagnosed with diabetes under 25 years of age.…”
mentioning
confidence: 99%
“…The YDR defined diabetes in youth as the onset of any type of diabetes in persons less than 25 years of age. [ 2 3 ] In the USA, the SEARCH for Diabetes in Youth (SEARCH) study, 2000, in five sites across the country, included youth diagnosed with diabetes under age 20 years. [ 4 ] It also assessed the natural history and risk factors for acute and chronic diabetes-related complications, quality of care, and quality of life.…”
mentioning
confidence: 99%
See 1 more Smart Citation